PROFIL HAMBATAN BELAJAR EPISTIMOLOGIS SISWA KELAS VIII SMP TERHADAP MATERI ENERGI DAN PERUBAHANNYA BERBASIS ANALISIS TES KEMAMPUAN RESPONDEN - Yunia Maghfirah; Heni Rusnayati; A. F. C. Wijaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Based on preliminary studies through questionnaire, test, and interviews, known that 52,12% students have been experiencing epistemological learning obstacles on energy and its transformation subject which is due to the limited context in comprehending a concept, and more than 50% students havenÃ¢â‚¬â„¢t able yet in doing the task with energy and its transformations. The objective of this study is to acknowledge the epistemological learning obstacles in 8th grade students on energy and its transformation subject based on respondents ability test analysis results. This study held with a qualitative descriptive method with historical approach analysis using respondents ability test which is a written essay test consists of five questions that cover energy and its transformation essential matter which were given to the students who had learned about energy and its transformation in one of public junior high school in Bandung Barat Regency. The result shows that 83,3% students experienced obstacles in determining the relation between velocity and kinetic energy, 86,11% in determining the relation between height and potential energy, 100% in determining the amount of produced energy compared to used energy in energy transformation concept, also 88,89% in applying the concept of conservation of energy in free fall motion case.Keywords: learning obstacles, respondents ability test, energy and its transformation.